Associations between pathophysiological traits and symptom development in retrospective analysis of V30M and V122I transthyretin amyloidosis - Sameer U. Kini; Ha My Thi Vy; Madhav Subramanian; Parasuram M. Krishnamoorthy; Son Q. Duong; Ghislain Rocheleau; Jagat Narula; Ron Do; Girish N. Nadkarni (International Journal of Cardiology: Heart & Vasculature)
Background: The Val30Met (V30M) and Val122Ile (V122I) transthyretin (TTR) mutations often beget hereditary amyloid transthyretin amyloidosis (hATTR). Since symptoms are progressively debilitating and potentially fatal if untreated, low survival rates result from late diagnoses of hATTR patients. This retrospective analysis of microarray and biobank data helped establish clinical biomarkers for early hATTR detection. Methods: In a Portuguese sample of V30M carriers (n = 183), gene profiling identified dysregulated immune markers. Among African Americans (AA) and Hispanic/Latinx Americans (HA) from the Mount Sinai BioMe Biobank (n = 28,718), a case-control style Phenome-Wide Association Study (PheWAS; odds ratio [95% confidence interval]) of V122I for phenotypic and echocardiogram traits (β coefficients [95 % CI]) determined gene pleiotropy. Results: Among V30M profiles, 96 (52.4%) were symptomatic, expressing upregulated neutrophil activity (p < 10-16), IL-6/JAK/STAT3 signaling (p < 10-3), and downregulated CD4+T cell expression (p = 0.009), compared to their asymptomatic counterparts. In BioMe, 562 (2.0%) were V122I carriers, demonstrating associations with heart failure (1.71 [1.23–2.39]; p = 0.0014), amyloidosis (20.79 [8.42–51.31]; p = 4.67 × 10−11), secondary/extrinsic cardiomyopathies (17.73 [7.25–43.37]; p = 2.97 × 10−10), peripheral nerve disorders (4.14 [2.42–7.09]; p = 2.26 × 10−7), primary angle-closure glaucoma (8.03 [3.15–20.46]; p = 1.27 × 10−5), malignant neoplasm of the female breast (4.48 [2.23–9.00]; p = 2.48 × 10−5), fracture of tibia and fibula (8.42 [3.25–21.89]; p = 1.19 × 10−5), and Carpal tunnel syndrome (2.62 [1.68–4.11]; p = 2.44 × 10−5). Echocardiographic presentations included higher LVEDV (15.87 [9.63–22.10]; p = 6.04 × 10−7) and LA length (1.52 [0.69–2.35]; p = 3.31 × 10−4). Race-stratified associations identified that AA presented more severe cardiac abnormalities than HA. Conclusions: This study identified inflammatory biomarkers upregulated in symptomatic V30M carriers and phenotypic/echocardiographic traits associated with V122I, representing comorbidities of hATTR pathology. Such markers can provide the basis for future improvements in diagnostic regimes to deliver early therapies.